Prevalence and Presentation of Paediatric Coronavirus Disease 2019 in Lagos, Nigeria - Abideen Salako; Oluwatosin Odubela; Tomilola Musari-Martins; Priscilla Ezemelue; Titilola Gbaja-Biamila; Babasola Opaneye; Ayorinde James; Osaga Oforomeh; Kazeem Osuolale; Adesola Musa; Emelda Chukwu; Nurudeen Rahman; et al. (International Journal of Pediatrics)
Background. The objective of this study was to describe the prevalence and clinical features of coronavirus disease 2019 (COVID-19) among children (≤18 years) evaluated for Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection at a testing centre in Lagos, Nigeria. Methodology. This was a retrospective study. Data on the sociodemographic, clinical characteristics and SARS-CoV-2 results of participants at a modified drive-through centre for COVID-19 test sample collection over four months were retrieved from the electronic medical records (EMR). Data obtained were analyzed using SPSS version 22.0. Results. A total of 307 children (≤18 years) were evaluated in this review. The prevalence of SARS-CoV-2 infection among the paediatric population was 16.3%. The median age (interquartile range (IQR)) was 9 (4–14) years. Common symptoms reported by the positive cases were fever (40.0%), cough (32.9%), sore throat (17.1%), and runny nose (15.7%). The majority of the positive cases had mild symptoms. Fever and sore throat were associated with the positive cases. Conclusion. Fever and sore throat were associated with SARS-CoV-2 infection among our cohort which buttresses the need for a high level of suspicion and clinical acumen in the management of common febrile diseases in paediatric settings.